PERSONALITY PECULIARITIES OF PREGNANT WOMEN EXPECTING THEIR FIRST CHILDREN - O. S. Zharkova (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
The first pregnancy and its outcome have great importance for the subsequent development of the individual as the subject of women of reproductive behavior, family relationships as well as the effectiveness of the professional selfrealization. It is known that personality traits affect the enjoyment by women of reproductive function. The article presents the results of a study to determine the role of age-related factors in the formation of personality traits and mental health of pregnant women with the birth of a child under the present conditions of socialization. The study was conducted in antenatal maternity Tomsk during 2003-2007 years, there have been psychological examination of 102 healthy pregnant women aged 19-37 years who were waiting for their first child. The study was conducted by a continuous method on a voluntary basis. Number of pregnant women under 20 years was 22, of 20-25-year-olds -42 and of 26 year olds and older - 38 women. Average age - 25,4 years, mean duration of pregnancy - 19 weeks. To study the structure and personality traits women test MMPI was used. Emotional relationship of pregnant women to significant persons and situations, partly bypassing the verbal defense mechanisms were examined by Etkind's color relationships. Computer processing and data analysis were performed using standard Microsoft Office programs and applied statistical package Statistica 6.0. The study showed that women in the period of pregnancy were characterized by an invariant state of personal, psychic sphere, which has both age determination and due to previous experience of sex-role behavior. At the same time there are typological differences not only in the structure of personality traits, but also in the features of value orientations and outlook of women, depending on the experience of their socialization as subjects of sexual and reproductive behavior. In particular, older women revealed the presence of a kind of "psychological defense" to explain the reasons for the relatively late birth of their first child. The study results complement the current theoretical understanding of the psychological aspects of female reproductive function, allows us to offer solutions to a number of important scientific and practical and social problems.